Automorphisms of Fuchsian Groups of Genus Zero - Md Tap, Abu Osman (1988)
Every automorphism in Fuchsian group is induced by some automorphism of a free group. This paper gives a presentation of a automorphism group of Fuchsian group of genus zero via braid groups. We also obtained the pure mapping class groups and the Seifert Fibre Groups.